2(4x-1)+3(3-2x)=0

Simple and best practice solution for 2(4x-1)+3(3-2x)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(4x-1)+3(3-2x)=0 equation:


Simplifying
2(4x + -1) + 3(3 + -2x) = 0

Reorder the terms:
2(-1 + 4x) + 3(3 + -2x) = 0
(-1 * 2 + 4x * 2) + 3(3 + -2x) = 0
(-2 + 8x) + 3(3 + -2x) = 0
-2 + 8x + (3 * 3 + -2x * 3) = 0
-2 + 8x + (9 + -6x) = 0

Reorder the terms:
-2 + 9 + 8x + -6x = 0

Combine like terms: -2 + 9 = 7
7 + 8x + -6x = 0

Combine like terms: 8x + -6x = 2x
7 + 2x = 0

Solving
7 + 2x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + 2x = 0 + -7

Combine like terms: 7 + -7 = 0
0 + 2x = 0 + -7
2x = 0 + -7

Combine like terms: 0 + -7 = -7
2x = -7

Divide each side by '2'.
x = -3.5

Simplifying
x = -3.5

See similar equations:

| 7+n=2n | | 4x+17=8x+10 | | 3a-9=7+3a-a | | 6x-3(x+9)=5x-17 | | (3x^2)+18x-16=2-7x | | 3(x-11)=14*34(16+x)-78 | | -6(3m-10)=6-9m | | 30y^2-25y+5=0 | | y^2-121=0 | | y+5=10 | | -[8z-(15z+8)]=8+(6z+2) | | -17p-5(2-5p)=4(p-4)-38 | | X^2+25x+600=0 | | -24=v+2 | | x^2+4x+2=y | | x-14=22 | | 2.7-2y=3 | | -19=14+x | | 25+x=50 | | 64k^2=16 | | 2.5-2y=4 | | -12=p+9 | | 4+a=2 | | -14=v+2 | | 20+k=27 | | x+2*2=6 | | -15+m=-22 | | k-10=-22 | | 2-2y=4 | | 26x^2-27x=0 | | -2p^2= | | 25x^3+10x^2-15x= |

Equations solver categories